The relationship between major life events and non-suicidal self-injury among college students: the effect of rumination and body image - Qin, Qian; Yang, Guangni; Li, Yue; Wu, Wanchun; Wang, Jianping; Chen, Ziyao; Kong, Xiaohua; Zhang, Wei; Zou, Hongyu (Frontiers in Public Health, 2024)
Non-suicidal self-injury (NSSI) poses a growing risk to public health worldwide.While numerous studies have identified major life events as key risk factors for NSSI, the mechanisms by which emotional and cognitive problems mediate or moderate this relationship remain unclear. In order to enhance the understanding of this field, we will draw upon the cascade theory of self-injury and the benefits and barriers model.This study aimed to examin how rumination mediates the relationship between major life events and NSSI. Additionally, this study further investigated the moderating effect of body image on the relationship between major life events and NSSI, as well as the relationship between rumination and NSSI. A sample of 2717 College Students (Mage = 19.81 years; SD = 1.09) participated in this study and anonymously completed the questionnaires. The results showed that rumination mediated the positive relationship between major life events and NSSI. Furthermore, body image was found to moderate both the relationship between major life events and NSSI, as well as the relationship between rumination and NSSI. The current findings suggest that rumination is an important mediator in the relationship between major life events and NSSI among college students. Teachers, parents, and researchers should recognise the important role of college students' body image self-perceptions, and actively promote a healthy and accurate body image.